Manual and software‐based measurements of treatment zone parameters and characteristics in children with slow and fast axial elongation in orthokeratology. (2nd April 2022) - Guo, Biyue; Wu, Huihuan; Cheung, Sin Wan; Cho, Pauline
Abstract: Purpose: To compare the treatment zone (TZ) measurements obtained using manual and software‐based methods in orthokeratology (ortho‐k) subjects and explore the TZ characteristics of children with slow and fast axial elongation after ortho‐k. Methods: Data from 69 subjects (aged 7 to <13 years old), who participated in three 24‐month longitudinal orthokeratology studies, showing fast (>0.27 mm, n = 38) and slow (<0.09 mm, n = 31) axial elongation, were retrieved. The TZ after ortho‐k was defined as the central flattened area enclosed by points with no refractive power change. TZ parameters, including decentration, size, width of the peripheral steepened zone (PSZ), central and peripheral refractive power changes and peripheral rate of power change, were determined manually and using python‐based software. TZ parameters were compared between measurement methods and between groups. Results: Almost all TZ parameters measured manually and with the aid of software were significantly different ( p < 0.05). Differences in decentration, size and the PSZ width were not clinically significant, but differences (0.45 to 0.92 D) in refractive power change in the PSZ were significant, although intraclass coefficients (0.95 to 0.98) indicated excellent agreement between methods. Significantly greater TZ decentration, smaller TZ size and greater inferior rate of power change (relative to the TZ centre) were observed in slow progressors using both methods, suggesting a potential role of TZ in regulating myopia progression in ortho‐k. Conclusion: TZ measurements using manual and software‐based methods differed significantly and cannot be used interchangeably. The combination of TZ decentration, TZ size and peripheral rate of power change may affect myopia control effect in ortho‐k.